Metagenomic Approaches to Analyze Antimicrobial Resistance: An Overview - de Abreu, Vinicius A. C.; Perdigão, José; Almeida, Sintia (Frontiers in Genetics, 2021)
Bacterial resistance, a major global public health problem, develops when pathogens acquire antimicrobial resistance genes (ARGs), primarily through genetic recombination between commensal and pathogenic microbes. The resistome is the collection of all ARGs. In microorganisms, the main method of ARG acquisition is horizontal gene transfer (HGT). Thus, understanding and identifying HGTs can provide insights into the mechanisms of resistance transmission and dissemination. The use of high-throughput sequencing technologies has made the analysis of ARG sequences feasible and accessible. In particular, the use of a metagenomic approach has facilitated the identification of community-based antimicrobial resistance. The metagenomic approach is useful as it allows access to the genomic data in an environmental sample without the need to isolate and culture microorganisms prior to analysis. Our goal was to reflect on the challenges of analyzing metagenomic data using the three main approaches for studying antimicrobial resistance: (i) analysis of microbial diversity; (ii) functional gene analysis, and (iii) searching the main resistome databases.